Performance analysis of a low pressure discharge thermal energy combined desalination unit. (5th February 2015) - Hosseini Araghi, A.; Khiadani, M.; Lucas, G.; Hooman, K.
Abstract: This study proposes a novel steam recovery cogeneration system, which is based on the low temperature thermal desalination (LTTD) system and named Low Pressure-Discharge Thermal Energy Combined Desalination (LP-DTECD). This technology includes open water and closed power cycles. Utilizing discharged thermal energy from a waste steam in an ammonia plant to cogenerate water and power is one significant of this system. Also, using an eductor instead of a steam jet ejector or a rotary vacuum pump to save valuable steam and make a convenient operation is another merit of the proposed technology. The mixture of NH3 –H2 O is utilised as working fluid for its closed Rankin cycle. A 28% improvement in the exergy flow was noted as in comparison with the energy waste of the base case. Utilising the LP-DTECD system is economical and demonstrates an improved CO2 emission reduction by 7%. Highlights: The LP-DTECD is a new steam recovery system. The LP-DTECD cogenerates water and power without any external fossil energy. It utilises an eductor to generate vacuum in the single desalinator and save the valuable steam. This system is a good option for coupling to a plant where discharge steam emits to the environment. The proposed system is a well economic and energy efficient choice.